2016
DOI: 10.1099/jgv.0.000522
|View full text |Cite
|
Sign up to set email alerts
|

IFN-λ4 desensitizes the response to IFN-α treatment in chronic hepatitis C through long-term induction of USP18

Abstract: The recently discovered interferon lambda 4 (IFN-l4) is a new member of the human type III interferons which could induce a strong antiviral effect through the JAK-STAT cascade. However, hepatitis C virus (HCV) patients who are capable of expressing IFN-l4 usually have poor response to IFN-a treatment, and the mechanism behind this paradox remains unknown. Here, we reported that IFN-l4 desensitized IFN-a-stimulated JAK-STAT signalling. Microarray analysis revealed that IFN-l4 could induce ubiquitin specific pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…USP18 was proposed as a key inhibitor of anti-HCV activity of IFNα (37, 49, 50), with attenuation of USP18 expression correlating with restoration of intrahepatic IFNα signaling and success of IFN-free HCV therapy (6, 9). Our analysis of ISG expression in liver biopsies pre- and post-treatment with DAA, showed that HCV-associated increase in USP18 expression occurred only in individuals that can produce IFN-λ4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP18 was proposed as a key inhibitor of anti-HCV activity of IFNα (37, 49, 50), with attenuation of USP18 expression correlating with restoration of intrahepatic IFNα signaling and success of IFN-free HCV therapy (6, 9). Our analysis of ISG expression in liver biopsies pre- and post-treatment with DAA, showed that HCV-associated increase in USP18 expression occurred only in individuals that can produce IFN-λ4.…”
Section: Discussionmentioning
confidence: 99%
“…In PHH treated with IFN-λ4 compared to IFN-λ3, USP18 protein expression was induced faster (already at 8 hrs), but consequences of this faster induction on the IFN response are unclear. Treatment of a hepatic cell line (Huh7) with IFN-λ4 led to a sustained induction of USP18 , making cells refractory to IFNα stimulation, but kinetics of USP18 expression induced by IFN-λ4 vs. other IFNs was not explored (49). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fan et al . also demonstrated that IFN-λ4 inhibits the JAK–STAT signalling pathway by inducing USP18 expression 28 . However, our current study showed the expression of IFN-λ4 after HCV infection for the first time.…”
Section: Discussionmentioning
confidence: 98%
“…HCV clearance was also associated with more rapid down-regulation of endogenous hepatic ISGs. Studies from our group and others clearly demonstrated that USP18 play a critical role in host innate immune response against HBV and HCV infections [ 11 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%